2018
DOI: 10.1371/journal.pone.0196232
|View full text |Cite
|
Sign up to set email alerts
|

FTI-277 inhibits smooth muscle cell calcification by up-regulating PI3K/Akt signaling and inhibiting apoptosis

Abstract: BackgroundVascular calcification is associated with increased cardiovascular morbidity and mortality in patients with atherosclerosis, diabetes and chronic kidney disease. However, no viable treatments for this condition have been identified. This study aimed to determine whether farnesyl transferase inhibitors (FTIs) can reduce vascular calcification and the mechanism by which this reduction occurs.ResultsWe demonstrate that FTI-277 significantly inhibits phosphate-induced mineral deposition by vascular smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Under high-phosphate circumstances, apoptosis or necrosis of VSMCs is induced [14,68,71,72], possibly generating apoptotic bodies from VSMCs, which could serve as nidi for calcium phosphate precipitation [71,73]. Phosphate-regulated intracellular signaling includes Wnt/β-catenin, protein Vascular smooth muscle cells (VSMCs) under hyperphosphatemic conditions.…”
Section: Vascular Smooth Muscle Cell Phenotypic Differentiation In Himentioning
confidence: 99%
See 1 more Smart Citation
“…Under high-phosphate circumstances, apoptosis or necrosis of VSMCs is induced [14,68,71,72], possibly generating apoptotic bodies from VSMCs, which could serve as nidi for calcium phosphate precipitation [71,73]. Phosphate-regulated intracellular signaling includes Wnt/β-catenin, protein Vascular smooth muscle cells (VSMCs) under hyperphosphatemic conditions.…”
Section: Vascular Smooth Muscle Cell Phenotypic Differentiation In Himentioning
confidence: 99%
“…Under high-phosphate circumstances, apoptosis or necrosis of VSMCs is induced [14,68,71,72], possibly generating apoptotic bodies from VSMCs, which could serve as nidi for calcium phosphate precipitation [71,73]. Phosphate-regulated intracellular signaling includes Wnt/β-catenin, protein kinase B (PKB or Akt), nuclear factor-kappa B (NF-κB), and serum-and glucocorticoid-inducible kinase 1 (SGK1) [57,[73][74][75][76]. The role of the inflammasome is also important [77,78].…”
Section: Vascular Smooth Muscle Cell Phenotypic Differentiation In Himentioning
confidence: 99%
“…Previous studies showed that high extracellular phosphate levels induce apoptosis and necrosis of VSMCs [ 1 , 2 , 16 , 46 ]. Under such circumstances, VSMCs release apoptotic bodies, which could serve as a nidus for calcium phosphate deposition [ 1 , 42 , 54 , 56 ]. In addition, apoptosis of VSMCs may lead to medial VSMC loss and degeneration as well as elastin breaks, cyst-like structures, and changes in extracellular matrix composition within the medial layer of the arteries [ 55 , 57 ], effects that may also contribute to vascular mineralization [ 2 , 7 , 43 ].…”
Section: Mechanisms Of Vascular Calcification In Hyperphosphatemiamentioning
confidence: 99%
“…AKT (also known as protein kinase B) signaling contributes to the complex machinery underlying VSMC osteoinduction [ 56 , 100 , 101 ]. Phosphate reduces AKT phosphorylation in VSMCs [ 56 , 100 ], while both pro-calcific effects [ 101 ] and protective effects against vascular calcification [ 101 , 102 ] of AKT activation have been described. AKT and SGK1 are able to phosphorylate and inactivate glycogen synthase kinase 3 (GSK-3) [ 103 , 104 ].…”
Section: Signaling Pathways Regulating Vsmcs Calcification During Higmentioning
confidence: 99%
“…Previous studies found that activation of PI3K/AKT signaling increases MGP expression (Mirsaidi et al , 2017; Ponnusamy et al , 2018). Although the crosstalk of JAK2/STAT5 signaling and PI3K/AKT signaling has been reported (Britschgi et al , 2012; Khanna et al , 2018), the underlying mechanisms remain largely unknown.…”
Section: Discussionmentioning
confidence: 91%